Social Emotional Learning Competencies in Belize Children: Psychometric Validation Through Exploratory Structural Equation Modeling - Hinerman, Krystal M.; Hull, Darrell M.; Näslund-Hadley, Emma I.; Mirzaei Rafe, Mehri (Frontiers in Psychology, 2022)
In the nation of Belize, and in particular the south side of Belize City, the main metropolitan area of the nation, significant economic disparities have led to child and adolescent exposure to high rates of violent crime, gang activity, unsafe neighborhoods, sexual and physical violence. Problems associated with poor Social-Emotional Character Development are especially prevalent among boys. Consequently, valid culture-relevant measures are required that identify problematic behavior for policy-based intervention and evaluation of educational programs designed to ameliorate this problem. The present study demonstrates the application of Exploratory Structural Equation Modeling to existing measures through the investigation of structural validity and generalizability of the Social-Emotional and Character Development Scale with a large sample of children from schools in Belize (N = 1,877, Ages 10 to 13). Exploratory structural equation modeling. Results demonstrate the original factor correlations were reduced, providing less biased estimates than confirmatory factor analysis. Moreover, a multi-group Exploratory Structural Equation Modeling analysis illuminates significant differences between latent factor scores of males and females for most factors. Using this newer factor analytic procedure, original factors are reconceptualized to better situate the Social Emotional Character Development Scales into the larger body of Social-Emotional Learning competencies literature.